2021
DOI: 10.1002/jemt.23975
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences between anemophilous and entomophilous pollen

Abstract: In order to provide a palynological guide for the identification of insect-carrying pollen grains, we studied the pollen grains of 10 anemophilous species and 10 entomophilous species in the Beijing urban area using light and scanning electron microscopies. We found that anemophilous pollen grains are small, spheroidal, or oblate spheroidal, while entomophilous pollen grains are medium and oblate. Comparison of the exine thickness and surface ornamentation showed that anemophilous pollen grains have significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The suspended pollens would also be detrimental to indoor air quality . The anemophilous flower pollens were dominant because of smaller cell size compared to the entomophilous flower …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspended pollens would also be detrimental to indoor air quality . The anemophilous flower pollens were dominant because of smaller cell size compared to the entomophilous flower …”
Section: Resultsmentioning
confidence: 99%
“…45 The anemophilous flower pollens were dominant because of smaller cell size compared to the entomophilous flower. 46 Humulus is a perennial herb and typical anemophily grass, widespread in most areas of China. It has a flowering period between August and October each year.…”
Section: Diversities and Community Structures Of Pollen In Ac Filtersmentioning
confidence: 99%
“…Pollen grains possess a wide range of different morphologies, sizes, and surface patterns [ 8 ]. A variation in morphology occurs between entomophilous (pollinated by insects) and anemophilous (wind pollinated) [ 9 ]. Elaborate morphologies in entomophilous plant pollens are important for pollinators attachment and adherence to the stigma surface; these pollens are protein-rich, heavy, and sticky in order to aid this process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smoother morphologies may be found in pollen from anemophilous grass and tree species. These pollens may also possess air sacs and will often be extremely lightweight to facilitate the wind pollination [ 9 ]. These different morphologies could be exploited as bio-templates for the production of various biomaterials with defined and hierarchical architecture in the same way in which the natural process of bio-mineralisation uses complex organic templates to create minerals with multiscale architecture [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several floristic studies have revealed the rich diversity and structure of the Caatinga biome (Araújo et al 2010;Santos et al 2011;Lima et al 2012;Sanquetta et al 2014;Luna et al 2015;Rocha et al 2017), as well as studies focusing on bee plant species for the Caatinga and other ecosystems. The description of pollen morphology from these areas, coupled with palynological analyses of bee products, has contributed to the identification of plant species foraged by bees, including the species Apis mellifera L. (Ferguson & Skvarla 1982;Aguiar et al 2002;Almeida et al 2006;Lima et al 2006;Viana et al 2006;Almeida 2007;Chaves et al 2007;Vidal et al 2008;Oliveira et al 2010;Nascimento et al 2014;Silva et al 2014a;Silva et al 2016b;Costa et al 2018;Rasoloarijao et al 2019;Mander et al 2020;Moraes et al 2020;Silva et al 2020;Lu et al 2021;Reis et al 2021;Dias et al 2022). A. mellifera forages to flowers for both pollen and nectar.…”
Section: Introductionmentioning
confidence: 99%